Correlation between bright echogenic liver, elevated liver enzymes and liver histology (Journal of Dhaka National Medical College & Hospital, 2012)
A total of 30 cases having bright echogenic liver on ultrasonography and raised ALT levels without Hepatitis B and Hepatitis C infection and without having history of alcohol consumption were referred to Gastroenterology department of BIRDEM Hospital and selected for liver biopsy in the study. The patients BMI and demographic profiles were recorded and necessary biochemical tests were carried out. After obtaining the histopathological reports, the correlation between different possible risk factors including biochemical findings and histological findings was sorted out. Based on BMI of Asian population, 73.4% of patients were over weight, 23.3% were obese and only 3.3% were with normal BMI. 90% patients presented with diabetes and 80% had some form of dyslipidaemia. 41% patients exhibited hypertriglycerdaemia, 21% had hypercholesterolaemia and both cholesterol and triglyceride were high in 34% patients. Histopathological study revealed that all 30 patients exhibited fatty change with macrovesicular type being the predominant. 43.3% patients had mild (